Expectations, stagnation and fiscal policy - George W. Evans; Seppo Honkapohja; Kaushik Mitra (Bank of Finland, 2016)
Stagnation as the new norm and fiscal policy are examined in a New Keynesian model with adaptive learning determining expectations. We impose inflation and consumption lower bounds, which can be relevant when agents are pessimistic. The inflation target is locally stable under learning. Pessimistic initial expectations may sink the economy into steady-state stagnation with deflation. The deflation rate can be near zero for discount factors near one or if credit frictions are present. Following a severe pessimistic expectations shock a large temporary fiscal stimulus is needed to avoid or emerge from stagnation. A modest stimulus is sufficient if implemented early.
URN:NBN:fi:bof-201608151375
Keywords: E62; D84; E21; E43; 330